Respuesta :
Answer:
[tex]n=\frac{-p^{3} }{(1+p^{2})(1+p)(1-p) }[/tex]
Step-by-step explanation:
To find the value of n we must solve the equation for n.
The equation can be written as:
[tex]n + p^{3} = np^{4}\\[/tex]
We are going to move the terms with n to the left and the terms without n to the right:
[tex]n + p^{3} = np^{4}\\n-np^{4} =-p^{3}[/tex]
Now we will proceed to factor the left side of the equation and solve for n:
[tex]n-np^{4} =-p^{3}\\n(1-p^{4})=-p^{3} \\n(1+p^{2})(1-p^{2} )=-p^{3} \\n(1+p^{2} )(1+p)(1-p)=-p^{3} \\n=\frac{-p^{3} }{(1+p^{2})(1+p)(1-p) }[/tex]
Therefore [tex]n=\frac{-p^{3} }{(1+p^{2})(1+p)(1-p) }[/tex]